Mental Health and Socio-Economic Outcomes in Burundi - Baingana, Florence; Dabalen, Andrew; Menye, Essimi; Prywes, Menahem; Rosholm, Michael (World Bank, Washington, DC, 2013)
This paper presents analysis of data from a survey of 5,599 respondents aged 10 years and older conducted country-wide in Burundi in 1998-99. The paper estimates statistically significant relationships between indicators of poor mental health and several social and economic outcomes. Most importantly, a worsening of mental health is associated with a decline in employment and with a decline in school enrollment of the subject's children. No relationship is found between mental health and poverty, once adjustments are made for demographic and regional influences. It argues that poor mental health diminishes people's participation in work and investment in their children's education through dysfunction resulting from psychiatric trauma and depression. Economic theory holds that investment in human capital, such as in education, will depend in part on expectations about the return on the investment.